Tsetse control, land use and livestock in the development of the Zambezi valley, Zimbabwe: Some policy considerations - Barrett, J.C. (International Livestock Centre for Africa, 1989)
Throughout Africa the importance of land use issues in relation to tsetse control planning has been emphasized consistently in the tsetse literature. Because of inappropriate land use, concerns for the environment in tsetse-freed areas have been expressed frequently. This debate is very relevant to Zimbabwe, where extensive tsetse control operations in recent years have confined the remaining area of tsetse infestation to parts of the Zambezi valley, a semi-arid region of the country with a fragile eco-system and limited agricultural potential. The government of Zimbabwe has ambitious plans for rural development in the valley, including proposals for tsetse control and the expansion of agro-pastoral farming. This paper examines the socio-economic objectives behind plans for development of the Zambezi valley and the arguments for and against tsetse control operations in support of sustainable rural development in Zimbabwe. Topics od discussion include land use planning and overstocking.